2014
DOI: 10.5296/ijafr.v3i2.4489
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of International Financial Reporting Standards (IFRS) in Ghana and the Quality of Financial Statement Disclosures

Abstract: According to the IASB's IFRS framework, qualitative characteristics are the attributes that make the information provided in financial statements useful to others. This study was conducted to investigate the quality of financial reports before and after adopting IFRSs in Ghana, and also the influence of firm-specific characteristics which include firm size, profitability, debt equity ratio, liquidity and audit firm size on the quality of financial information disclosed by firms listed on the Ghana Stock Exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 37 publications
1
46
0
Order By: Relevance
“…(a) Signaling theory: The argument of the theory is that companies comply and disclosed information in financial statements to signal superior performance for shareholders, potential investors, corporate and regulatory bodies including other market participants. Barde (2009) and Ben (2013) argued in different dimensions that compliance to International Accounting Standards by profitable companies is one way of signaling their superior performance to the market.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…(a) Signaling theory: The argument of the theory is that companies comply and disclosed information in financial statements to signal superior performance for shareholders, potential investors, corporate and regulatory bodies including other market participants. Barde (2009) and Ben (2013) argued in different dimensions that compliance to International Accounting Standards by profitable companies is one way of signaling their superior performance to the market.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Attitudes towards the adoption of IFRS have been examined in various countries (see for example, Grrece: Papadatos and Bellas, 2011;Dritsas and Petrakos, 2014; Nigeria: Madawaki, 2012;Ikpefan and Akande, 2012;Odia and Ogiedu, 2013;Herbert, Tsegba, Ohanele, and Anyahara, 2013;Okunbor and Arowoshegbe, 2014; Malaysia: Sidik and Abd Rahim, 2012;Hanefah and Singh, 2012; India: Patro and Gupta, 2012;Athma and Rajyalaxmi, 2013;Bhargava and Shikha, 2013;Vinayagamoorthy, 2014. USA: Djatej, Zhou, Gorton, andMcGonigle, 2012;Joos and Leung, 2013; Hong Kong: Helen and Kh, 2013; Ghana: Mensah, 2013;Abedana, Omane-Antwi, and Oppong, 2016; Turkey: Chebaane and Othman, 2013;Balsari and Varan, 2014;Kılıça, Uyar and Ataman, 2014;Vietnam: Phan, Mascitelli, and Barut, 2014. Libya: Zakari, 2014; Bangladesh: Hossain et al, 2015a;Hossain, Hasan,and Safiuddin, 2015b; Australia: Bodle, Cybinski, & Monem, 2016).…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
“…They advised accounting professionals and education providers to develop materials on IFRS. Mensah (2013) examined the quality of financial reports of firms listed on the Ghana Stock Exchange before and after adopting IFRS. He found that company size, represented by net assets and auditor type are statistically associated with the quality of financial information disclosed.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
“…The high leverage ratio is to be expected as the biggest component of the sample being commercial and investment banks. Auditor type was simply categorized as big four (1) and non-big four (2). The results show that around 83% (30 of the 36 companies in the sample) of the listed companies in Bahrain are audited by a big four firm.…”
Section: Descriptive Statisticsmentioning
confidence: 99%